Hidden Symmetry from Supersymmetry in One-Dimensional Quantum Mechanics - Andrianov, A.A.; Sokolov, A.V. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
When several inequivalent supercharges form a closed superalgebra in Quantum Mechanics it entails the appearance of hidden symmetries of a Super-Hamiltonian. We examine this problem in one-dimensional QM for the case of periodic potentials and potentials with finite number of bound states. After the survey of the results existing in the subject the algebraic and analytic properties of hidden-symmetry differential operators are rigorously elaborated in the Theorems and illuminated by several examples.